PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING DENGAN TEKNIK NUMBERED HEADS TOGETHER TERHADAP KEAKTIFAN DAN PEMAHAMAN KONSEP SISWA PADA MATA PELAJARAN EKONOMI: Studi Eksperimen Pada Siswa Kelas X SMA Pasundan 1 Bandung - Putra, Angga (2014)
PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING DENGAN TEKNIK NUMBERED HEADS TOGETHER TERHADAP KEAKTIFAN DAN PEMAHAMAN KONSEP SISWA PADA MATA PELAJARAN EKONOMI (Studi Eksperimen Pada Siswa Kelas X SMA Pasundan 1 Bandung) The problem in this research is the lack of understanding of the concept and less active students in learning. The purpose of this study was to determine the Influence of Cooperative Learning Model Technique Numbered Heads Together Against Concept Training Activity and Lesson In Economics Students. Subjects of this study there are class X-1 daan X-2 SMA Pasundan 1 Bandung. The method used in this study is a quasi experimental method (Quasi Experimental. The design used in this study are non equivalent (pre-test post-test) control-group design. The instrument used in this study a written test of 30 multiple choice matter. Data analysis conducted with two sample t test unrelated and independent samples t-test (independent sample test). The results showed that there were differences being categorized on student learning outcomes in economic subjects in the experimental class before and after treated, there low category differences in learning outcomes of students in economic subjects in the control group before and after being treated, there is a difference in student learning outcomes in economic subjects between class and class control experimentation after being treated. There are differences in the level of activity of students in economic subjects between classes control and experimental classes. Recommendations for teachers should be able to choose the teknik smart learning that affect the understanding of concepts and student activity.